Laparoscopic diagnosis and treatment of nonpalpable testis - Denes,Francisco T. (2008)
INTRODUCTION: Treatment of the cryptorchid testicle is justified due to the increased risk of infertility and malignancy as well as the risk of testicular trauma and psychological stigma on patients and their parents. Approximately 20% of cryptorchid testicles are nonpalpable. In these cases, the videolaparoscopic technique is a useful alternative method for diagnosis and treatment. MATERIALS AND METHODS: We present data concerning 90 patients submitted to diagnostic laparoscopy for impalpable testicles. Forty-six patients (51.1%) had intra-abdominal gonads. In 25 testicles of 19 patients, we performed a two stage laparoscopic Fowler-Stephens orchiopexy. The other 27 patients underwent primary laparoscopic orchiopexy, in a total of 29 testicles. RESULTS: We obtained an overall 88% success rate with the 2 stage Fowler-Stephens approach and only 33% rate success using one stage Fowler-Stephens surgery with primary vascular ligature. There was no intraoperative complication in our group of patients. In the laparoscopic procedures, the cosmetic aspect is remarkably more favorable as compared to open surgeries. Hospital stay and convalescence were brief. CONCLUSIONS: In pediatric age group, the laparoscopic approach is safe and feasible. Furthermore, the laparoscopic orchiopexy presents excellent results in terms of diagnosis and therapy of the impalpable testis, which is why this technique has been routinely incorporated in our Department.